The Effectiveness of the Listening Triangle and Responsibility Circle Strategies in Acquiring Practical Mechanics and Managing Time for Completing Laboratory Experiments among First-Year Physics Students (Journal of the College of Basic Education, 2026)
The current research aims to determine the effectiveness of the Listening Triangle strategy and the Responsibility Circle strategy in improving the achievement of practical mechanics students and their time management skills for conducting laboratory experiments. To achieve this objective, null hypotheses formulated, and an experiment conducted over the course of a full semester that is the first semester of the academic year. The research population consisted of first-year physics students at the College of Education, Mustansiriyah University. A purposive sampling method used to select a sample of 72 students. Equivalence between the two groups have ensured through the variables of age (in months), prior knowledge, and time management. The necessary equipment for the experiment has developed, including an achievement test, as no suitable tests were available for this research. Additionally, a time management scale was developed and its psychometric properties verified. After the students completed all laboratory experiments, the research groups tested using the developed instruments. Data analysis revealed that the first experimental group outperformed the second and control groups in both achievement and time management, while the second experimental group outperformed the control group in the dependent variables. In light of these results, a set of recommendations and suggestions made for conducting subsequent studies to complement the current research.